An empirical study on maternal and perinatal outcome of placenta previa-risk factors, morbidity and mortality in JNIMS, Imphal, India - Sanglakpam, Haripriya Devi; Ng., Indrakumar Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The observational study to analyse the maternal and perinatal outcome in pregnancies complicated with placental previa evaluating the potential risk factor, associated with morbidity and mortality. Methods: The study was a prospective longitudinal comprising of all the pregnant women after 28 week of gestation irrespective of gravid and parity that attended or admitted in the department of obstetrics and gynaecology, JNIMS, diagnosed as having placental previa by transabdominal ultrasonography and conducted for the period of 20 months i.e. from October 2017 to June 2019 analyzing 54 cases of placenta previa. Results: During this period there were total of 9967 deliveries with incidence of placenta previa being 0.54% in JNIMS, Porompat. The estimated risk factors out of total 54 cases were 20-30 (52%) years by age group, 25 (46%) gravida, 18 (32%) parity, 36 low lying placenta and 11 cases (20%) preterm. Conclusions: Highest levels of placenta previa are associated with poor maternal and perinatal outcome.